THE EFFECT OF PROFITABILITY, FIRM SIZE, AND CAPITAL STRUCTURE ON FIRM VALUE IN MANUFACTURING COMPANIES - Widiarta, Jessica Rosalina; Dermawan, Elizabeth Sugiarto (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to determine the effect of profitability, firm size, and capital structure on firm value of manufacturing companies in consumer non-cyclical sub-sector listed on the Indonesia Stock Exchange (IDX) during 2020-2022. There are 140 data used as samples which were taken from 49 consumer non-cyclical companies listed on Indonesia Stock Exchange (IDX) for three years in a row. Samples were taken based on purposive sampling techniques, one of non probability sampling methods which was determined by selected criteria. Data used for this reseach is secondary data which is the annual reports from 2020-2022. This research uses multiple regression analysis and helped by Microsoft Excel and SPSS program version 29. Refering to signaling theory and trade-off theory, assumption in this research that are used as hypotheses in this study are profitability has positive and significant effect on firm value, firm size has positive and significant effect on firm value, and capital structure has negative and significant effect on firm value. The results of this study find that profitability has positive and significant effect on firm value, firm size has negative and insignificant effect on firm value, and capital structure has positive and significant effect on firm value. Simultaneous, profitability, firm size, and capital structure have significant effect on firm value.